Kontribusi Media Pembelajaran Daring terhadap Minat Belajar Siswa - Nazyumei Arbah; Rini Sefriani; Astri Indah Juwita (Universitas Putra Indonesia YPTK Padang, 2021)
This study aims to determine the contribution of online learning media to students' interest in learning in network service technology subjects for class XI Smk Negeri 8 Padang. The type of this research is correlational quantitative, the sampling is done using the Proportion Random Sampling technique. Total 66 people. The instrument used in data collection in this study was a questionnaire compiled according to the Likert scale model. Data analysis was performed using SPSS 20 and Microsoft Excel. Based on the results of the study, the value of rcount -0.212 while the value of rtable is 0.250 because the value of rcount is smaller than the value of rtable is 0.212 < 0.250) it can be concluded that there is no significant relationship between online learning media and student interest in learning, with a contribution value of 4.5% which means that online learning contributes to students' interest in learning in network service technology subjects is very low. which means that online learning contributes to students' interest in learning in network service technology subjects is very low.